ANALISIS PENGARUH EPS DAN DPR TERHADAP HARGA SAHAM PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wendy Utomo, Laurensius Steven; L. Tobing, Vargo Christian (LPPM Universitas Putera Batam, 2022)
This study aims to determine the effect of earnings per share (EPS) and dividend payout ratio (DPR) on stock prices of food and beverage sub-sector companies on the Indonesia Stock Exchange partially and simultaneously. The research method used is the classical assumption test, multiple linear analysis, hypothesis testing, and the coefficient of determination test. The independent variables in this study are earnings per share (EPS) and dividend payout ratio (DPR), while the dependent variable is stock price. The population of this study were 34 food and beverage sub-sector companies for the 2016-2020 period. The sampling technique used purposive sampling technique and got 9 companies with a total sample of 45. The data used is secondary data from financial reports published by the Indonesia Stock Exchange for the 2016-2020 period through the website www.idx.co.id. Stock price data is obtained from the website www.yahoofinance.com using the annual closing price. Based on this study, earnings per share (EPS) partially have a significant effect on stock prices, while the dividend payout ratio (DPR) partially has no significant effect on stock prices. Simultaneously, earnings per share and dividend payout ratio have a significant effect on stock prices.